Wing area optimization for box wing aircraft - Paul Olugbeji, Jemitola; Ekene Gabriel, Okafor; Abbe, Godwin (International Journal of Engineering and Technology, 2019)
The optimization of the wing area of a medium range box wing aircraft was carried out in this study using a multidisciplinary conceptual design/optimization approach based on gradient search algorithm and regression analysis. The methodology was also applied to a similar sized conventional cantilever wing aircraft and the result generated an optimal wing area similar to the real wing area of the cantilever aircraft considered, thereby validating the methodology.Â NomenclatureAUM: All up MassDOC: Direct Operating CostCDo: Zero Lift Drag Coefficient: Wing Sweep Angle: Wing Average Thickness to Chord RatioSubscript: Aft WingF: Fore WingÂ